2015
DOI: 10.1007/s10585-015-9735-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression array analysis of the hepatocyte growth factor invasive program

Abstract: Signaling by human hepatocyte growth factor (hHGF) via its cell surface receptor (MET) drives mitogenesis, motogenesis and morphogenesis in a wide spectrum of target cell types and embryologic, developmental and homeostatic contexts. Oncogenic pathway activation also contributes to tumorigenesis and cancer progression, including tumor angiogenesis and metastasis, in several prevalent malignancies. The HGF gene encodes full-length hHGF and two truncated isoforms known as NK1 and NK2. NK1 induces all three HGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…These results demonstrate the causative role of CAF-produced HGF in this model of resistance. Notably, while mouse HGF was reported to activate only some of the MET-driven biological activities in human cells (Cecchi et al, 2015), we clearly observed that, in the specific context of resistance to MET TKIs, mouse and human purified HGF exerted superimposable effects on human MET-addicted cells, inducing a similar shift of the TKI IC 50 ( Figure 2G).…”
Section: Increased Hgf Production By Cafs Is Responsible For Adaptivementioning
confidence: 66%
“…These results demonstrate the causative role of CAF-produced HGF in this model of resistance. Notably, while mouse HGF was reported to activate only some of the MET-driven biological activities in human cells (Cecchi et al, 2015), we clearly observed that, in the specific context of resistance to MET TKIs, mouse and human purified HGF exerted superimposable effects on human MET-addicted cells, inducing a similar shift of the TKI IC 50 ( Figure 2G).…”
Section: Increased Hgf Production By Cafs Is Responsible For Adaptivementioning
confidence: 66%
“…HGF and NK1, but not NK2, induce epithelial tubulogenesis [28]. NK2 enhances the migration of cells and antagonizes the mitogenic response induced by HGF or NK1 [29][30][31]. A synthetic Met agonist composed of cyclic peptide weakly activated Met but enhanced cell motility at levels comparable to that of HGF [32].…”
Section: Distinct Activation Of the Met-related Signaling Pathway By Nk1 And Hgf Mutantsmentioning
confidence: 99%
“…To investigate this possibility, we exploited the inability of mouse HGF to fully activate human MET [2628]. In fact, MET activation in colorectal tumors occurs primarily via paracrine HGF stimulation by the surrounding stroma [29].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we hypothesized that HGF/MET signaling could be responsible not only for allowing CRC cells to physically escape anti-angiogenic therapy, but also for rewiring their metabolism in response to vessel pruning. To investigate this possibility, we exploited the inability of mouse HGF to fully activate human MET [ 26 28 ]. In fact, MET activation in colorectal tumors occurs primarily via paracrine HGF stimulation by the surrounding stroma [ 29 ].…”
Section: Introductionmentioning
confidence: 99%